Sir James Frazer - Hutton, Ronald (New Age Movements, Occultism, and Spiritualism Research Library, 2023)
The author of the Golden Bough was as remarkable as his book, in his professional career, personal life, and political, social and religious attitudes; and these things all deeply informed his approach to scholarship. This address is devoted to explaining how and why this was, and to suggesting which of his ideas are still relevant to the present day, and which are not. Additional Authors: Shaking the Tree, Breaking the Bough: Frazer's Golden Bough at 100 (Conference); Tully, Caroline Jane; Budin, Stephanie Lynn; University of Melbourne;
"Sir James Frazer." Paper presented at the Shaking the Tree, Breaking the Bough: Frazer's Golden Bough at 100, Melbourne, Australia, February 10, 2023
1 video file. ms150-40-002_hutton-ronald_sir-james-frazer_2023-02-10.mp4 .mp4 2.73 GB 2,927,061,959
Keywords: Frazer, James George, 1854-1941. Golden bough; Frazer, James George, 1854-1941.; Conference papers and proceedings; Literary criticism; Video recordings